ANALISIS UNDANG-UNDANG PERKAWINAN TERHADAP ANALYSIS OF MARRIAGE LAW ON MINIMUM AGE LIMITS OF MARRIAGE - Hazna Hazna (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
The revision of Act Number 1 of 1974 entered into discussion in the National Legislation Program (prolegnas) 2015-2019. The revision should be done because the values in the formulation of the Marriage Act is not in accordance with social protection measures and there are many shows non-compliance with the rules of article. Besides the purpose of the Marriage Act is regulating the marital life to be controlled by marriage administratively and can affect citizen identification. Indecision of Marriage Law, especially against the minimum age of marriage causes many losses, especially in women and children. The practice shows there are still many parents who marry off their children under the age of set for marriage, Based on that background the author proposes two fundamental issues: how the limit of age for marriage according to the religion, customs and laws. And why we are need for revision the Marriage Act regarding the minimum age limit of marriage. The result of this research and discussion made a conclusion that are differences of the determination for the age of the child at each legislations, but basically the set of 18 years old as a child can be held the responsibility, but on the Marriage Act for the woman's age, is 16 years old. Then the revision of Marriage Act can avoid the occurence of early marriage.